Efficacy and Safety of Oral Chinese Patent Medicine Combined with Conventional Therapy for Heart Failure: An Overview of Systematic Reviews. (27th August 2020) - Lin, Shan-Shan; Liu, Chun-Xiang; Zhang, Jun-Hua; Wang, Xian-Liang; Mao, Jing-Yuan
Abstract : Objectives . By performing an overview of systematic reviews and meta-analyses of the efficacy and safety of oral Chinese patent medicine combined with conventional therapy in the treatment of heart failure, to evaluate the reliability and applicability of the conclusions of the current studies and provide evidence for clinical decision-making. Methods . Systematic reviews and meta-analyses of oral Chinese patent medicine combined with conventional therapy treating heart failure were searched based on standardized search strategy in six electronic databases including PubMed, Embase, Cochrane Library (No. 2 of 2020), China National Knowledge Infrastructure (CNKI), Wanfang Database (Wanfang), and Chinese Scientific Journal Database (VIP) from inception to February 2020. The literature was independently screened and extracted by two researchers. The methodological quality of the included literature was evaluated using the AMSTAR-2 (A Measurement Tool to Assess Systematic Review 2). If necessary, we would summarize the original research data and further perform data synthesis using RevMan software (version 5.3), and the evidence quality of the included literature was graded using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. Results . A total of 38 systematic reviews and meta-analyses were included, involving 11 kinds of oral Chinese patent medicines, including Qili Qiangxin Capsules (11/38), Qishen Yiqi Dropping Pills (9/38), Shexiang Baoxin Pills (4/38), Wenxin Keli (2/38), Tongxinluo Capsules (2/38), Compound Danshen Dripping Pills (2/38), Zhenyuan Capsules (3/38), Buyi Qiangxin Tablets (2/38), Yangxinshi Tablets (1/38), Xuezhikang (1/38), and Yixinshu Capsules (1/38). The methodological quality of all literature was rated as critically low. The grading of the quality of evidence was 43 moderate, 101 low, and 40 very low. The main reason for the degradation of evidence quality was the risk of bias. In the evaluation of efficacy, there was no statistically significant difference between the two groups in terms of mortality, which is a piece of low-quality evidence. Qili Qiangxin Capsules or Qishen Yiqi Dripping Pills combined with conventional therapy can significantly reduce the hospitalization rate of patients with chronic heart failure, and the quality of the evidence is moderate. The overall efficacy of oral Chinese patent medicine combined with conventional therapy in improving the clinical symptoms, quality of life, exercise endurance, laboratory tests, physical examination, and other indicators of patients with heart failure is confirmed. In the evaluation of safety, there was no significant difference between the two groups. Conclusions . Oral Chinese patent medicine combined with conventional therapy has good clinical efficacy and safety in the treatment of heart failure. However, due to its low level of methodological quality and evidence quality, the current evidence-based conclusions need to be further verified.